2015
DOI: 10.1016/j.jad.2015.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of subjects with mood disorders in the Lundby community cohort: A follow-up over 50 years

Abstract: Mortality of subjects with mood disorders in the LundbyLink to publication Citation for published version (APA): Mattisson, C., Bogren, M., Brådvik, L., & Horstmann, V. (2015). Mortality of subjects with mood disorders in the Lundby community cohort: A follow-up over 50 years. Journal of Affective Disorders, 178, 98-106. DOI: 10.1016/j.jad.2015 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The principal psychiatric diagnosis for both types of suicide was depressive disorder, since undertreated depression was the most frequently found mental illness in suicide31 and suicide was more prevalent among those with mood disorders 32. Our finding of no difference in the rate of depressive disorder between the 2 groups supports previous findings that depression is not linked to any specific type of suicide 33.…”
Section: Discussionsupporting
confidence: 84%
“…The principal psychiatric diagnosis for both types of suicide was depressive disorder, since undertreated depression was the most frequently found mental illness in suicide31 and suicide was more prevalent among those with mood disorders 32. Our finding of no difference in the rate of depressive disorder between the 2 groups supports previous findings that depression is not linked to any specific type of suicide 33.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies generally found a higher mortality burden of depression among men than women. 33,34 However, these studies followed single cohorts of individuals and thus could not assess secular trends in gender differences in mortality associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…High radiation anxiety was also observed in residents (Orita et al 2013;Hino et al 2016). The perception of high radiation risk is associated with mental stress , which, along with mood disorders, is a major risk factor for suicide and other causes of death (Pratt 2009;Mattisson et al 2015). Further, multiple studies reported that after the 2011 accident, the subjective well-being of people living in the area around the Nuclear Power Station declined (Hommerich 2012;Rehdanz et al 2015;Tiefenbach and Kohlbacher 2015).…”
Section: Introductionmentioning
confidence: 99%